Vigor tests association as an alternative for precise and efficient assessment of maize seed quality. - DIAS, M. A. N. (2015)
This study aimed to associate two concepts of seed vigor testing, the aging and seedling growth using image analysis, providing a feasible and time-saving way to evaluate maize seed vigor in large scale. For this purpose, five seed lots with different vigor levels from two single hybrids were used. The seeds were char-acterized by moisture content, germination, seedling emergence, seedling emergence speed index, accelerated aging and cold tests. The treatments were composed by varying the accelerated aging periods (0, 24, 48, 72 and 96h) and seedling growth periods (48 and 72h), before submitting the seedlings to image analysis for seedling root length measurement. Considering the results obtained, the adaptation of accelerated aging test by reducing the aging duration from 96h to 48h, and the replacement of the germination test by seedling root length meas-urement using image analysis could be considered a potential tool for maize seed vigor assessment. The treat-ments composed of 48h of seed aging followed by seedlings root length measurements using image analysis provided reliable data, compared to traditional vigor tests and it could be considered an efficient and time-saving approach, associating two different concepts of seed vigor analysis.